Sustained expression of fis, the gene coding for the Fis nucleoid-associated protein, during the stationary phase of growth in Salmonella enterica - Guadarrama-Beltrán, Seratna (Trinity College (Dublin, Ireland). School of Genetics and Microbiology, 2013)
The Factor for Inversion Stimulation (Fis) is a global regulator of virulence genes in Salmonella enterica serovar Typhimurium. Previously, the Fis protein was throught to be expressed only during the early exponential phase of growth, but work in our research group has shown that fis gene expression can be sustained into the stationary phase when the bacteria are grown under conditions of low aeration. This finding is significant because Fis is known to be a global regulator of many Salmonella virulence genes and low aeration growth is used routinely to maximize the infectivity of Salmonella during in vitro infection studies. The underlying molecular mechanism responsible for this unusual pattern of fis gene expression has now been investigated.
Keywords: Genetics & Microbiology, Ph.D.; Ph.D. Trinity College Dublin.